Mediating Role Of Brand Image In Digital Marketing And E-WOM On Islamic Bank Customer Decisions - Maulidia, Farah Esti; Adha, Mufti Alam; Wahyudi, Rofiul (JPS (Jurnal Perbankan Syariah), 2024)
The present study aims to analyze the effects of digital marketing and Electronic Word of Mouth (E-WOM) on brand image, then examine the effects of digital marketing and Electronic Word of Mouth on the decision to be an Islamic bank customer and analyze the effects of digital marketing and Electronic Word of Mouth on the decision to be an Islamic bank customer through brand image as a mediating variable. The research type used in the present study was quantitative, using primary data obtained by distributing questionnaires. By distributing questionnaires, 100 respondent data was found and analyzed using SPSS version 26. The sampling techniques used by the author were the snowball sampling technique and nonprobability sampling. The criteria for the research sample were Islamic bank customers and social media users. Because the size of the research population was unknown, the present study used Lemeshow’s formula. The research results showed that digital marketing had a significant effect on brand image, Electronic Word of Mouth had a considerable effect on brand image, and digital marketing significantly affected the decision to become an Islamic bank customer. In contrast, Electronic Word of Mouth did not significantly affect the decision to be an Islamic bank customer. Brand image positively and significantly affects the decision to become a customer.